Evaluation of Parkinson’s Disease Treatment Information in Internet - Baran, Gözde (Cerrahpaşa Medical Journal, 2022)
Objective: The aim of this study is to determine the quality of the information presented on the websites about “Parkinson's Disease Treatment” and “Parkinson’s Disease Surgery” and their role in patient information by evaluating the DISCERN® scores and author classification of the researched websites. Methods: The search words were determined as “Parkinson’s disease treatment (PDT)” and “Parkinson’s disease surgery (PDS)” from Google®. The first 30 websites were evaluated with the DISCERN® instrument. Results: A total of 60 websites were analyzed with 2 different searches with the keywords. When section 1 results were evaluated, the purposes of 2 (7.1%) websites in the Parkinson’s disease treatment group and 2 (6.7%) websites in the Parkinson’s disease surgery group were clear and understandable. When section 2 results were evaluated, 3 websites (10.7%) in the Parkinson’s disease treatment group and 10 websites (33.3%) in the Parkinson’s disease surgery group explained all treatment methods. When the section 3 results were evaluated, 3 (10.7%) websites out of 28 websites in the Parkinson’s disease treatment group and 3 (10%) websites out of 30 websites in the Parkinson’s disease surgery group were found to be useful and appropriate sources of information, based on the answers to all other questions. Conclusion: To prevent patients from accessing misleading information on the internet and to prevent information pollution, it is recommended to monitor websites and to rely more on websites containing information from health professionals. Cite this article as: Baran G. Evaluation of parkinson’s disease treatment information in internet. Cerrahpaşa Med J. 2023;47(1):77-80.